Kehidupan Buruh Perkebunan Teh Kayu Aro Tahun 1925 – 1943 - Agustin Putri Lestari; Nirwan Il Yasin (Jurnal Siginjai, 2021)
The purpose of this paper is to examine the development of plantations and the lives of workers in the Kayu Aro tea plantation, which is one of the largest tea plantations in Indonesia. Focus discussion lies in the life of Kayu Aro tea plantation workers using a socio-economic approach. The results of this study indicate socio-economic conditions of Kayu Aro tea plantation workers who are mostly imported from Java because of difficulty of finding workers around the plantation, which was once an uninhabited forest, has differences, especially with plantations in East Sumatra, which is an area with a community of workers from Java which is huge. This difference is influenced by the location of the plantation, time or period, government policies, company management and the environment. Kayu Aro tea plantation was founded in 1925 by NV.HVA (Namlodse Venotchaaf Handel Vereniging Amsterdam). Kayu Aro tea plantation was planned by NV.HVA to be the largest and widest tea plantation in its time so that everything that supports the plan is well prepared. Kayu Aro tea plantation workers in the colonial period received high wages and had good relations with plantation management making the labor situation better than plantation workers in East Sumatra.